Polymer tensiometers with ceramic cones: direct observations of matric pressures in drying soils - M. J. van der Ploeg; H. P. A. Gooren; G. Bakker; C. W. Hoogendam; C. Huiskes; L. K. Koopal; H. Kruidhof; G. H. de Rooij (Hydrology and Earth System Sciences, 2010)
Measuring soil water potentials is crucial to characterize vadose zone processes. Conventional tensiometers only measure until approximately −0.09 MPa, and indirect methods may suffer from the non-uniqueness in the relationship between matric potential and measured properties. Recently developed polymer tensiometers (POTs) are able to directly measure soil matric potentials until the theoretical wilting point (−1.6 MPa). By minimizing the volume of polymer solution inside the POT while maximizing the ceramic area in contact with that polymer solution, response times drop to acceptable ranges for laboratory and field conditions. Contact with the soil is drastically improved with the use of cone-shaped solid ceramics instead of flat ceramics. The comparison between measured potentials by polymer tensiometers and indirectly obtained potentials with time domain reflectometry highlights the risk of using the latter method at low water contents. By combining POT and time domain reflectometry readings in situ moisture retention curves can be measured over the range permitted by the measurement range of both POT and time domain reflectometry.